The development of early childhood caries impact on quality of life-Indonesia instrument as assessment instrument of dental caries impact on quality of life of children aged 3-5 years based on Indonesian community characteristics - Taufan Bramantoro; Yayi Suryo Prabandari; Djauhar Ismail; Udijanto Tedjosasongko (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Improvement of quality of life is one of objectives in establishment of healthcare system according to World Health Organization policy. Studies of dental health-related factors that influence quality of life of children aged 3-5 years have not been developed yet, particularly in Indonesia. Previous study which adopted international instruments has some limitations of inappropriate characteristics of question items with local community characteristics. Quality of life assessment could describe sociodemographic status and community cultural background, as well as varies of special characteristics in a community group, related to oral and dental health features with sensitivity to the difference of age group. Purpose: This study was aimed to develop early childhood caries impact on quality of life-Indonesia (ECCIQOL-INA) as assessment instrument of dental caries impact on quality of life of children aged 3-5 years based on Indonesian community characteristics. Method: Initially, this study was conducted qualitatively using Focus Group Discussion method, validity and reliability test, subsequently the study was continued using quantitative method as a cross-sectional analytical study to analyze the utilization of instrument in 309 children aged 3-5 years enrolled in kindergarten and early childhood education programs (ECEP) with their mothers at working area of Community Health Centre Wates in Mojokerto. Result: There were four question items as assessment instrument of dental health problems that impact on quality of life on children aged 3-5 years, i.e, “Has your child ever been irritable/restless?” (“Apakah anak Ibu pernah merasa rewel/gelisah?”), “Has your child ever refused to eat and drink or felt discomfort while eating and drinking?” (“Apakah anak Ibu pernah tidak mau atau tidak enak makan dan minum?”), “Has your child ever been absent from school?” (“Apakah anak Anda pernah tidak masuk sekolah?”) “Has your child ever been difficult or unable to sleep?” (“Apakah anak Ibu pernah tidak bisa tidur atau sulit tidur?”). Conclusion: ECCIQOL-INA instrument had been successfully developed and could be utilized as assessment instrument of dental caries impact on quality of life on children aged 3-5 years based on Indonesian community characteristics.